The challenges of higher education in Colombia: Reflections from trend analysis - Andrade Navia, Juan Manuel (2024)
This article aims to analyze the challenges that higher education in Colombia will have in the coming years based on the analysis of national and international trends. The study was mixed in nature and descriptive in nature in which multiple data collection techniques were used. Initially, the analysis of documentary sources was used to collect the information of interest and, subsequently, the Delphi survey and the Regnier Abacus were used, with the participation of experts, to prioritize relevant trends. In this regard, thirty-two (32) national and international trends are identified, among which aspects such as the global and regional scarcity of resources, the development of ICT, the increase in climate change, the expansion of nanotechnology and the technological convergence, among others. Subsequently, due to the large number of trends, they were systematized and consolidated into four (4) future vectors, namely: 1) Demography; 2) Resources; 3) Technology; 4) Higher Education Institutions. Finally, based on the vectors, three scenarios were constructed that constituted challenges for higher education in Colombia.